2022
DOI: 10.1097/md9.0000000000000232
|View full text |Cite
|
Sign up to set email alerts
|

Top of basilar artery infarction

Abstract: Rationale: The posterior circulation represents 20% of blood supply to the brain, and its occlusion, commonly by embolism, causes brainstem, cerebellar, and lower cerebral infarctions. The clinical presentation varies from mild symptoms to severe neurological deficits or death. The duration of intervention is vital, commonly with antithrombotic drugs or through intervention. Patient concerns: The first case was a 36-year-old-female admitted due to snake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…He concluded that the emergency intervention helps in the recovery of the patients. 7 In our case patient presented with decreased consciousness and slurring of speech and on further evaluation patient diagnosed as Top of basilar artery syndrome and treated accordingly. Risk factors in our case include hypertension, chronic smoker and alcoholic.…”
Section: Introductionmentioning
confidence: 65%
“…He concluded that the emergency intervention helps in the recovery of the patients. 7 In our case patient presented with decreased consciousness and slurring of speech and on further evaluation patient diagnosed as Top of basilar artery syndrome and treated accordingly. Risk factors in our case include hypertension, chronic smoker and alcoholic.…”
Section: Introductionmentioning
confidence: 65%